Терминологијата од областа на информатичкото општество во македонскиот јазик: дефинирање и создавање терминолошки бази на податоци - Мицкоски, Николче (Филолошки факултет, УКИМ, Скопје, 2021)
Every language should strive to develop an appropriate terminology in various subject areas in order so that its speakers will not be forced to use terms from other language. People created monolingual and bilingual wordlists on clay tablets in the ancient times. For easier communication between speakers of different languages, bilingual and multilingual phrase books and dictionaries have been compiled over the years. The first Macedonian printed text is “A dictionary of four languages” (Greek, Albanian, Aromanian and Macedonian) by Daniil of Moscopole (first edition in 1794, second edition in 1802). Introductory section of this thesis provides an overview of the historical development of terminology and current situation in our country and partly in the word. The overview starts with the theory of terminology, from traditional terminology of Wüster and Lotte, through socioterminology of Gaudin and Temmerman, to the computational terminology of Pearson, as well as Cabré’s perspectives on theory and application of terminology. In addition, introductory section provides an overview of the created corpora that are analysed as well as the basic terminology used in this thesis. First chapter provides an overview of the two principles of creating terminology of information society: traditional principle with the concept in its centre and the new principle based on corpus linguistics. Terminologists should start using corpus linguistics because it provides quantitative and qualitative perspective of the text data and enables creating terminology based on relevant data. Official (de jure) and unofficial (de facto) standards for terminology are elaborated in the second chapter. This chapter provides an overview of the official standards published by the ISO/TC 37 Language and terminology within the International Organization for Standardization. The overview begins with the standards on principles and methods of terminology work, and ends with the standards on modelling, specification, design, documentation and encoding of digital language resources. Following official standards is necessary in order to enable exchange and reuse of a product on different platforms without limitations. The third chapter is dedicated to the word-formation. It provides an overview of the methods for formation of neologisms, as well as formation of new words based on the exiting words, i.e. derivation, compounding, creating abbreviated terms, expansion of semantic field of the general terms, semantic transfer within a special language, transdisciplinary borrowing and conversion. In addition, there is an overview of the basic principles for term formation: transparency (as opposed to vagueness), consistency, appropriateness, linguistic economy, productiveness, linguistic correctness and preference for native language. Analysis of the terms in the Glossary of Macedonian terms in the field of information technology showed that terms in the field of information society are usually nouns, and rarely verbs and adjectives. In the fourth chapter, there is an analysis of the practical use of information society terms, particularly in the subject fields of information technologies, electronic communications, audiovisual media services and malicious software and viruses. The analysis of acronyms showed that there are certain rules and guidelines for formation and use of the acronyms, but they are not clearly defined and need to be more precise. The analysis of the practical use of information society terms in the functional styles in Macedonian shows that in colloquial, publicistic, and scientific functional styles there is a prevalence of transliterated versions of English terms which do not follow the norms of Macedonian language, and there is an inconsistent use of different terms for denoting a single concept. Appropriate terms are dominant in the administrative functional style, although there are slight inconsistencies and incorrect terms. Research and analysis described in the fifth chapter show that a large variety of terms denoting the same concept are used and there is possibility to be used in the everyday life. For the 49 terms in the research, respondents suggested 1399 different terms that can be used as translation equivalents. The analysis of the translation memories from the localization projects of Microsoft, Samsung and Huawei showed that professional translators rarely use inconsistent terms. Chapter six provides a detailed proposal for the structural representation of a terminological entry in a terminology database. Applicability of the proposal is described with an example from the terminology bulletin on Publishing within the macro project Macedonian Scientific and Professional Terminology of Macedonian Academy of Sciences and Arts. Corpus linguistics should be a starting point for creating terminological dictionaries. Modern technologies enable digital representation of the terms by creating and maintaining terminology databases. The digital form of the terminology databases allows updating and adding new data, as well as exchange of the data in an appropriate and predetermined format. That will enable consistent use of defined terminology within the terminology subject field.
Information society terminology in Macedonian: defining and creating terminology databases
Докторска дисертација одбранета во 2021 година на Филолошкиот факултет во Скопје, под менторство на проф. д–р Емилија Црвенковска.